2022
DOI: 10.3390/molecules27092764
|View full text |Cite
|
Sign up to set email alerts
|

Losartan Alleviates the Side Effects and Maintains the Anticancer Activity of Axitinib

Abstract: Axitinib is one of the most potent inhibitors of the vascular endothelial growth factor (VEGF) receptor and shows strong antitumor activity toward various malignant tumors. However, its severe side effects affect the quality of life and prognosis of patients. Losartan, which functions as a typical angiotensin receptor blocker, controls the average arterial pressure of patients with essential hypertension and protects against hypertension-related secondary diseases, including proteinuria and cardiovascular inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recent 2022 publication demonstrated in animal models (Wistar rats) treated with Axitinib that losartan, an established angiotensin-receptor blocker, can be used to effectively reduce hypertensive effects without effect on antitumor activity. 68 A 2022 publication by Ren et al 69 found that in patients with metastatic CRC with bevacizumab-related hypertension, treatment with renin-angiotensin inhibitors showed significant survival benefits over patients treated with calcium channel blockers or no treatment. Interestingly Mice studies using lisinopril further demonstrated a positive synergistic antitumor effect with increased 5-fluorouracil tissue penetration and decrease both collagen and hyaluronic acid deposition whilst significantly downregulating the expression of TGF (transforming growth factor)-β1 and downstream SMAD (Small Mothers Against Decapentaplegic) signaling which may also improve antitumor effect.…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…Recent 2022 publication demonstrated in animal models (Wistar rats) treated with Axitinib that losartan, an established angiotensin-receptor blocker, can be used to effectively reduce hypertensive effects without effect on antitumor activity. 68 A 2022 publication by Ren et al 69 found that in patients with metastatic CRC with bevacizumab-related hypertension, treatment with renin-angiotensin inhibitors showed significant survival benefits over patients treated with calcium channel blockers or no treatment. Interestingly Mice studies using lisinopril further demonstrated a positive synergistic antitumor effect with increased 5-fluorouracil tissue penetration and decrease both collagen and hyaluronic acid deposition whilst significantly downregulating the expression of TGF (transforming growth factor)-β1 and downstream SMAD (Small Mothers Against Decapentaplegic) signaling which may also improve antitumor effect.…”
Section: Vascular Endothelial Growth Factor Inhibitorsmentioning
confidence: 99%
“…For these reasons, the side effects of Axitinib, a VEGFR inhibitor, occur in over 30% of patients and include diarrhea, hypertension, fatigue, loss of appetite, nausea, decreased kidney function, and anemia [ 90 , 91 ]. Since VEGFR is involved in the continuous renewal of capillaries, the blocking of these receptors could prevent the physiological repair of traumatized capillaries, facilitating the onset of bleeding.…”
Section: Side Effects and Resistance Phenomena Of Current Kismentioning
confidence: 99%
“…Entrectinib, [16] an inhibitor targeting tropomyosin receptor kinases (Trk), protooncogene tyrosine-protein kinase ROS1, and anaplastic lymphoma kinase (ALK), is indicated for metastatic non-small cell lung cancer (NSCLC) with ROS1 or NTRK gene fusions. Axitinib, [17][18] a vascular endothelial growth factor receptor (VEGFR) and platelet-derived growth factor receptor (PDGFR) inhibitor, finds its application in advanced renal cell carcinoma (kidney cancer) after prior systemic therapy. Lonidamine [19] possesses antineoplastic properties and has been explored for its potential in cancer treatment by disrupting cancer cell energy metabolism, although its adoption as a standard cancer treatment remains limited.…”
Section: Introductionmentioning
confidence: 99%